2020
DOI: 10.1096/fj.202001290r
|View full text |Cite
|
Sign up to set email alerts
|

The protective function of taurine on pesticide‐induced permanent neurodevelopmental toxicity in juvenile rats

Abstract: Numerous studies have confirmed that prenatal or early postnatal exposure to pesticides can lead to functional deficits in the developing brain. This study aimed to investigate whether combined exposure to paraquat (PQ) and maneb (MB) during puberty could cause permanent toxic effects in the neural system of rats. In addition, the neuroprotective function of taurine (T) and its possible mechanism were investigated. Rats were administered PQ + MB intragastrically for 12 continuous weeks, while taurine dissolved… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 59 publications
(102 reference statements)
0
2
0
Order By: Relevance
“…In rats treated orally with Mancozeb, dose-related signs of neurotoxicity were also noticed, including adynamia, muscular tone reduction, loss of motor coordination, paralysis of the lower limbs, loss of appetite, and prostration [ 16 , 17 ]. Adverse neurodevelopmental effects were also observed in rats fed with Maneb and Paraquat during puberty, which were prevented by adding taurine to the diet [ 96 ]. In vitro studies have shown that Zineb is capable of inducing apoptosis in SH-SY5Y human neuroblastoma cells, suggesting that the same effect would occur in dopaminergic neurons [ 97 ].…”
Section: Resultsmentioning
confidence: 99%
“…In rats treated orally with Mancozeb, dose-related signs of neurotoxicity were also noticed, including adynamia, muscular tone reduction, loss of motor coordination, paralysis of the lower limbs, loss of appetite, and prostration [ 16 , 17 ]. Adverse neurodevelopmental effects were also observed in rats fed with Maneb and Paraquat during puberty, which were prevented by adding taurine to the diet [ 96 ]. In vitro studies have shown that Zineb is capable of inducing apoptosis in SH-SY5Y human neuroblastoma cells, suggesting that the same effect would occur in dopaminergic neurons [ 97 ].…”
Section: Resultsmentioning
confidence: 99%
“…Combined exposure to paraquat and maneb reduced PKA production through cAMP stimulation and, thus, inhibited activating elements like BDNF, CREB, ARC, C-JUN, C-FOS, etc. [ 48 , 49 ]. Further, BDNF downregulation eventually reduces the Creb mRNA and protein levels through the MER/ERK pathway [ 50 ].…”
Section: Pesticides and Neurotoxicitymentioning
confidence: 99%